Anchor bolt and its manufacturing process and concrete component using the anchor bolt

By pre-embedding anchor bolts in the concrete component and fixing them with convex rings, the problem of inconvenient lifting operation in the prior art is solved, and the safe and reliable lifting of concrete components and the improvement of construction efficiency are achieved.

CN111139938BActive Publication Date: 2024-12-27重庆市云鹏水泥制品有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010028179.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-10
Publication Date
2024-12-27
Estimated Expiration
2040-01-10

AI Technical Summary

Technical Problem

The existing concrete prefabricated pipe gallery is inconvenient to operate during lifting. It is necessary to drill holes in the side walls of the pipe gallery and fix them with expansion bolts, resulting in complex and inconvenient operation.

Method used

Design an anchor bolt, including a bolt with threaded holes in the axial direction, a convex ring is fixed on the outer wall of the bolt, which is buried in the concrete member in advance and is covered after pouring, and is passed through the lifting bolt and the anchor bolt during lifting. Threaded connection to avoid additional holes and the convex ring prevents the cylinder from falling apart.

Benefits of technology

It realizes convenient lifting and safe transfer of concrete components, reduces on-site construction steps, and improves lifting performance and construction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111139938B_ABST
    Figure CN111139938B_ABST
Patent Text Reader

Abstract

The present invention relates to an anchor bolt and a manufacturing process thereof and a concrete member using the anchor bolt, and relates to the technical field of anchor bolts. The anchor bolt comprises a bolt barrel with a threaded hole axially arranged at one end, and at least one convex ring is fixedly arranged on the outer wall of the bolt barrel. The invention has the advantage that the concrete member is not easy to loosen when being hoisted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anchor bolts, and in particular to an anchor bolt and a manufacturing process thereof, and a concrete component using the anchor bolt. Background Art

[0002] With the development of society, precast concrete parts have been widely used in various projects, especially precast concrete pipes, which are developing better and better as important components in the construction of municipal underground pipeline corridors.

[0003] The prior art refers to a Chinese invention patent with authorization announcement number CN101586709B, which discloses a prefabricated concrete pipe gallery, which is composed of a gallery body and a corridor. The corridor is made in the gallery body, and the cross section of the corridor is square. The gallery body is cylindrical, and a receiving interface and an inserting interface are coaxially fixed at both ends of the gallery body. The invention has a simple structure and reduces the number of on-site construction steps. However, the invention has the following shortcomings: Since the surface of the pipe gallery is smooth, tools are generally used to drill holes in the side walls of the pipe gallery during the transfer and lifting process, and then expansion bolts are inserted into the pipe gallery for fixed connection before lifting operations are performed, which is inconvenient to operate. Summary of the invention

[0004] One of the purposes of the present invention is to provide an anchor bolt which has the advantages of being easy to lift and not easy to loosen after being pre-buried in a concrete component.

[0005] The above-mentioned object of the present invention is achieved through the following technical solutions:

[0006] An anchor bolt comprises a bolt barrel with a threaded hole arranged axially at one end, and at least one convex ring is fixedly arranged on the outer wall of the bolt barrel.

[0007] By adopting the above technical solution, when prefabricating concrete components, the anchor bolts are pre-buried in the mold before pouring. After the concrete solidifies, the bolt barrel and the convex ring are covered in the concrete. When lifting the concrete component, it is only necessary to connect the eye bolt with the anchor bolt thread to carry out the lifting and transfer operation, without the need to drill additional holes in the concrete component. Since the convex ring can effectively prevent the bolt barrel from detaching from the concrete, the lifting performance is reliable.

[0008] In a preferred example, the present invention can be further configured as follows: the bolt barrel is a plastic part, and the outer diameter of the bolt barrel gradually increases from the closed end of the threaded hole to the open end.

[0009] By adopting the above technical solution, on the one hand, plastic parts can be formed in one step by injection molding, which is conducive to mass production, and is more corrosion-resistant than metals, reducing costs; on the other hand, when the eye bolt is rotated into the plastic anchor, the outer wall of the anchor is tightly fixed by the concrete to prevent its outer surface from expanding. During the movement of the eye bolt, the eye bolt applies pressure to the end of the plastic anchor with a smaller outer diameter, so that the plastic anchor is effectively compressed around the eye bolt, and the eye bolt and the plastic anchor are less likely to loosen.

[0010] In a preferred example, the present invention can be further configured as follows: a side wall of the bolt barrel close to the open end of the threaded hole is extended along the axial direction of the threaded hole to form an extension tube, and the inner diameter of the extension tube is larger than the inner diameter of the threaded hole.

[0011] By adopting the above technical solution, the distance between the bolt barrel and the surface of the concrete component is increased when in use, making it more difficult for the anchor bolt to be separated from the component. The inner diameter of the extension tube is larger than the inner diameter of the threaded hole. When installing the eye bolt, the threaded section of the eye bolt can easily enter the threaded hole, and the extension tube plays a certain guiding role, which is convenient for operation.

[0012] In a preferred example, the present invention can be further configured as follows: the side wall edge of one end of the extension tube away from the plug barrel extends away from the axis to form a flange, and the cross-section of the flange is triangular.

[0013] By adopting the above technical solution, the flange blocks the gap between the extension tube and the concrete, and at the same time protects the concrete around the anchor bolt, preventing the concrete from peeling off and causing the anchor bolt connection strength to decrease. In addition, since the flange blocks the gap between the extension tube and the concrete, rainwater is not easy to leak into the interior from the joint between the anchor bolt and the concrete.

[0014] The third object of the present invention is achieved by the following technical solutions:

[0015] A production process for an anchor bolt, wherein the plastic is prepared from the following raw materials in parts by weight:

[0016] 80-90 parts of nylon 66, 10-20 parts of carbon fiber, 15-20 parts of carbon fiber intercalated graphene composite material, 8-12 parts of modified calcium carbonate, 0.5-1 parts of acrylate, 0.8-1.5 parts of zinc stearate, 1-2 parts of antioxidant, 0.8-1.5 parts of lubricant, 0.5-1 parts of stabilizer;

[0017] The preparation steps are as follows:

[0018] (1) Preparation of carbon fiber: Place cellulose nanofibers in a tubular furnace, then introduce protective gas, heat to 300-500°C at a rate of 2-5°C / min and keep warm for 1-3h, then heat to 700-1000°C at a rate of 5-10°C / min and keep warm for 0.5-2h, and finally cool to room temperature at a rate of 5-10°C / min to obtain carbon fiber material;

[0019] (2) Preparation of carbon fiber intercalated graphene composite materials: cellulose nanofibers are dispersed in an aqueous solution to prepare a 1wt% dispersion, and the dispersion is treated with ultrasound for 60-120 min, during which the temperature is controlled at 20-30°C; then a graphene oxide solution with a molar concentration of 1-2 mol / L is added to the dispersion and stirred for 10-20 min, and then ultrasonically treated for 30-60 min to obtain a uniformly dispersed dispersion of cellulose nanofibers and graphene oxide; then N2H4·H2O is added to the obtained cellulose nanofiber and graphene dispersion, and after stirring and dispersing evenly, The PH value of the system is adjusted to 10 by using NH3·H2O, and the mixture is stirred for 5-10 minutes. The reaction system is sealed, heated to 85-90°C, reacted for 60-120 minutes, rinsed with distilled water to neutrality by dialysis method, and freeze-dried to obtain a cellulose nanofiber intercalated graphene composite material; finally, the obtained cellulose nanofiber intercalated graphene composite material is placed in a tubular furnace, a protective gas is introduced, the temperature is increased to 700-1000°C at a heating rate of 5-10°C / min and kept at this temperature for 1-2 hours, and the temperature is decreased to room temperature at a cooling rate of 5-10°C / min to obtain a carbon fiber intercalated graphene composite material;

[0020] (3) Material mixing: Weigh the weight portions of nylon 66, carbon fiber, and carbon fiber intercalated graphene composite material, put them into a mixer and mix them evenly, then add the weight portions of modified calcium carbonate, acrylate, zinc stearate, antioxidant, lubricant, and stabilizer, mix them evenly, and obtain a uniformly mixed material;

[0021] (4) Injection molding: The uniformly mixed material in step (3) is put into an injection molding machine, and a plastic anchor bolt is obtained by injection molding and cooling.

[0022] By adopting the above technical solution, the structural strength of the anchor bolt and the service life of the internal thread are increased, and the use is safer.

[0023] The third object of the present invention is achieved by the following technical solutions:

[0024] A concrete component comprises at least one anchor bolt mentioned above which is buried and fixed, and the threaded hole of the anchor bolt is exposed.

[0025] By adopting the above technical solution, the concrete component comes with its own anchor bolt. When it needs to be transferred and lifted, it only needs to connect the eye bolt with the anchor bolt thread. The operation is convenient and the lifting is safe and reliable.

[0026] In a preferred example, the present invention can be further configured as follows: the concrete component is a tube body of a reinforced concrete structure, and the anchor bolt is fixed to the outer side wall of the tube body.

[0027] By adopting the above technical solution, the prefabricated concrete pipe body is easy to lift and transport, and is convenient for construction and transfer.

[0028] In a preferred example, the present invention can be further configured as follows: a metal sheath is coaxially fixed to one end of the tube body, a plug-in end matching the metal sheath is provided at the other end of the tube body, and a metal protective ring with the same outer diameter is fixed to the outer wall of the end of the plug-in end.

[0029] By adopting the above technical solution, when two adjacent pipe bodies are connected, the plug end of one pipe body can be inserted into the metal sheath of the other pipe body, and the connection part is protected by the metal sheath. In addition, the metal sheath and the metal protection ring jointly protect the two ends of the pipe body, reducing the possibility of the concrete pipe body being damaged.

[0030] In a preferred example, the present invention can be further configured as follows: an annular groove is provided on the outer wall of the plug end along the circumferential direction.

[0031] By adopting the above technical solution, when the two pipe bodies are connected, a rubber sealing ring can be pre-installed in the groove to improve the sealing performance of the connection between the two pipe bodies.

[0032] In summary, the present invention includes at least one of the following beneficial technical effects:

[0033] 1. When prefabricating concrete components, the anchor bolts are pre-buried in the mold before pouring. After the concrete solidifies, the bolt barrel and the convex ring are covered in the concrete. When lifting the concrete component, you only need to connect the eye bolt with the anchor bolt thread to carry out the lifting and transfer operation, and there is no need to drill additional holes in the concrete component. Because the convex ring can effectively prevent the bolt barrel from detaching from the concrete, the lifting performance is reliable;

[0034] 2. Plastic anchor bolts can be formed in one step by injection molding, which is conducive to mass production. Compared with metal, it is corrosion-resistant and reduces costs. On the other hand, when the eye bolt rotates into the plastic anchor bolt, the outer wall of the anchor bolt is tightly fixed by the concrete to prevent its outer surface from expanding. During the movement of the eye bolt, the eye bolt applies pressure to the end of the plastic anchor bolt with a smaller outer diameter, so that the plastic anchor bolt is effectively compressed around the eye bolt, and the eye bolt and the plastic anchor bolt are less likely to loosen.

[0035] 3. The prefabricated concrete pipe body is safe and reliable during construction and lifting, which improves construction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the overall structure of Example 1;

[0037] Figure 2 for Figure 1 Sectional view of the AA plane;

[0038] Figure 3 is a schematic structural diagram of a concrete component in Example 2;

[0039] Figure 4 Schematic diagram of the demoulding state of the concrete component in Example 2;

[0040] Figure 5 This is a partial schematic diagram of the anchor bolt connection state when pouring the concrete component in Example 2.

[0041] In the figure: 1. anchor bolt; 11. bolt barrel; 111. threaded hole; 12. first convex ring; 13. second convex ring; 14. flanging; 141. expansion hole; 142. chamfered corners; 15. extension tube; 2. eye bolt; 3. tube body; 31. plug-in end; 32. groove; 33. steel cage; 34. metal protective ring; 35. metal sheath; 4. mold; 41. upper mold shell; 411. perforation; 42. lower mold shell; 43. front cover; 44. rear cover. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0043] Embodiment 1:

[0044] refer to Figure 1 and Figure 2 , is an anchor bolt disclosed in the present invention, comprising a bolt barrel 11 with a threaded hole 111 and an open end, a first convex ring 12 is fixed to the outer wall of the open end of the bolt barrel 11, a second convex ring 13 is fixed to the outer wall of the closed end of the bolt barrel 11, and an extension tube 15 is formed integrally with the side wall of the open end of the bolt barrel 11 extending along the axis of the threaded hole 111.

[0045] The outer wall of the bolt barrel 11 has a contour radius that gradually increases from the closed end to the open end, so that the outer wall of the bolt barrel 11 is set at an angle α with the axis of the threaded hole 111, and α can be 5°-10°. The outer wall of the bolt barrel 11 can be provided with a plurality of convex ribs, so that after the anchor bolt 1 is buried in the concrete and fixed, the anchor bolt 1 will not rotate relative to the concrete when subjected to circumferential torsion.

[0046] The edge of the end of the extension tube 15 away from the threaded hole 111 is radially extended outward to form a flange 14, and the extension tube 15 is provided with a reaming hole 141 coaxially arranged and connected with the threaded hole 111, and the inner wall of the reaming hole 141 is smooth. The diameter of the threaded hole 111 is d1, and the diameter of the reaming hole 141 is d2, d2-d1 is 5-10mm, and the step position at the connection between the reaming hole 141 and the threaded hole 111 is smoothly transitioned through a rounded corner 142.

[0047] The outer diameter of the closed end of the bolt barrel 11 is D1, the outer diameter of the first bead 12 is D3, and the outer diameter of the second bead 13 is D2, D2=D3=1.1~1.2*D1, D1=1.3-1.5*d1.

[0048] The anchor bolt 1 can be made of engineering plastic or stainless steel and has high strength and deformation resistance.

[0049] Embodiment 2:

[0050] refer to Figure 3 , is a concrete component disclosed in the present invention, comprising a cylindrical hollow tube body 3 and an anchor bolt 1 embedded and fixed in the outer wall of the middle part of the tube body 3.

[0051] The pipe body 3 is made of concrete, and a cylindrical steel cage 33 is provided inside the pipe body 3, so that the pipe body 3 has good structural strength. A metal sheath 35 is fixed to the outer wall of one end of the pipe body 3, and the other end of the pipe body 3 is a plug-in end 31 whose outer wall contour radius is equal to the inner diameter of the metal sheath 35. A metal protective ring 34 is fixed to the outer wall of the end of the plug-in end 31 away from the metal sheath 35 along the circumferential direction. The metal protective ring 34 and the metal sheath 35 can increase the impact resistance of the outer wall at both ends of the pipe body 3, and reduce the possibility of damage and cracking of the edges at both ends of the pipe body 3.

[0052] The outer wall of the plug end 31 is circumferentially recessed to form an annular groove 32. When the two tube bodies 3 are spliced ​​end to end, the plug end 31 is inserted into the metal sheath 35. A rubber sealing ring can be pre-installed in the groove 32 to improve the sealing of the connection between the two tube bodies 3.

[0053] refer to Figure 4 and Figure 5 The concrete component is made and formed in the mold 4, which includes an upper mold shell 41 and a lower mold shell 42 that are arranged in a split manner. The upper mold shell 41 and the lower mold shell 42 are spliced ​​to form a cylindrical mold cavity. The joint between the upper mold shell 41 and the lower mold shell 42 is fixed by bolts and nuts; the two ends of the upper mold shell 41 and the lower mold shell 42 are respectively connected with an annular front end cover 43 and a rear end cover 44 by bolts.

[0054] A through hole 411 is provided in the middle of the upper mold shell 41 for the threaded column of the eye bolt 2 to pass through. The eye bolt 2 is threadedly connected with the anchor bolt 1 after passing through the through hole 411.

[0055] The production process of this concrete element is as follows:

[0056] Put the tied steel cage 33 on the lower mold shell 42, brush the mold release agent on the inner wall of the mold 4, and then assemble the mold 4. Align the open end of the anchor bolt 1 with the through hole 411 of the upper mold shell 41, and then pass the eye bolt 2 through the through hole 411 and thread it with the anchor bolt 1, so that the anchor bolt 1 is fixed to the upper mold shell 41.

[0057] The mold 4 can be moved by hooking the eyebolt 2 with a lifting device, and the assembled mold 4 is suspended on the roller shaft of the suspension roller machine, and the mixed concrete is poured into the mold 4 from both open ends to make a preliminary blank of the concrete component by the suspension roller process.

[0058] After the preform is manufactured, it is hoisted to a storage site together with the mold 4 by means of eyebolts 2, and the mold is removed after the concrete hardens to reach the strength standard.

[0059] refer to Figure 4 and Figure 5 Before removing the mold, first rotate the eyebolt 2 to separate it from the anchor bolt 1, remove the eyebolt 2, then remove the bolts on the mold 4, and lift the upper mold shell 41 away. Then, re-thread the eyebolt 2 and the anchor bolt 1, and use the lifting equipment to hook the eyebolt 2 to lift the concrete component away from the lower mold shell 42. After lifting, remove the eyebolt 2.

[0060] When the concrete components are transported later or hoisted during on-site construction, it is only necessary to reinstall the eyebolt 2 onto the anchor bolt 1, and the hoisting is safe and reliable.

[0061] Embodiment 3:

[0062] An anchor bolt, which is different from the embodiment 1 in that the anchor bolt is made of engineering plastics, and the plastics are prepared from the following raw materials in parts by weight:

[0063] 80 parts of nylon 66, 10 parts of carbon fiber, 15 parts of carbon fiber intercalated graphene composite material, 8 parts of modified calcium carbonate, 0.5 parts of acrylate, 0.8 parts of zinc stearate, 1 part of antioxidant, 0.8 parts of lubricant and 0.5 parts of stabilizer.

[0064] The preparation method of the plastic anchor is as follows:

[0065] (1) Preparation of carbon fiber: Cellulose nanofibers were placed in a tubular furnace, and then a protective gas was introduced. The temperature was raised to 300°C at a rate of 2°C / min and kept at that temperature for 1 h. The temperature was then raised to 700°C at a rate of 5°C / min and kept at that temperature for 0.5 h. Finally, the temperature was lowered to room temperature at a rate of 5°C / min to obtain carbon fiber material.

[0066] (2) Preparation of carbon fiber intercalated graphene composite materials: cellulose nanofibers were dispersed in an aqueous solution to prepare a 1 wt% dispersion, and the dispersion was treated with ultrasound for 60 min, during which the temperature was controlled at 20 °C; then a 1 mol / L graphene oxide solution was added to the dispersion and stirred for 10 min, followed by ultrasound treatment for 30 min to obtain a uniformly dispersed dispersion of cellulose nanofibers and graphene oxide; then N2H4·H2O was added to the obtained cellulose nanofiber and graphene dispersion, and stirred and dispersed. After being uniform, NH3·H2O was used to adjust the pH of the system to 10, and the mixture was stirred for 5 minutes. The reaction system was sealed, heated to 85°C, reacted for 60 minutes, and rinsed with distilled water to neutrality by dialysis method, and freeze-dried to obtain a cellulose nanofiber intercalated graphene composite material; finally, the obtained cellulose nanofiber intercalated graphene composite material was placed in a tubular furnace, a protective gas was introduced, the temperature was increased to 700°C at a heating rate of 5°C / min and kept at this temperature for 1 hour, and the temperature was decreased to room temperature at a cooling rate of 5°C / min to obtain a carbon fiber intercalated graphene composite material;

[0067] (3) Material mixing: Weigh the weight portions of nylon 66, carbon fiber, and carbon fiber intercalated graphene composite material, put them into a mixer and mix them evenly, then add the weight portions of modified calcium carbonate, acrylate, zinc stearate, antioxidant, lubricant, and stabilizer, mix them evenly, and obtain a uniformly mixed material;

[0068] (4) Injection molding: The uniformly mixed material in step (3) is put into an injection molding machine, and a plastic anchor bolt is obtained by injection molding and cooling.

[0069] Embodiment 4:

[0070] An anchor bolt, which is different from the embodiment 1 in that the anchor bolt is made of engineering plastics, and the plastics are prepared from the following raw materials in parts by weight:

[0071] 85 parts of nylon 66, 15 parts of carbon fiber, 18 parts of carbon fiber intercalated graphene composite material, 10 parts of modified calcium carbonate, 0.8 parts of acrylate, 1 part of zinc stearate, 1.5 parts of antioxidant, 1.2 parts of lubricant and 0.8 parts of stabilizer.

[0072] The preparation method of the plastic anchor is as follows:

[0073] (1) Preparation of carbon fiber: Cellulose nanofibers were placed in a tubular furnace, and then a protective gas was introduced. The temperature was raised to 500°C at a rate of 5°C / min and kept at that temperature for 1 h. The temperature was then raised to 1000°C at a rate of 10°C / min and kept at that temperature for 0.5 h. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to obtain carbon fiber material.

[0074] (2) Preparation of carbon fiber intercalated graphene composite materials: cellulose nanofibers were dispersed in an aqueous solution to prepare a 1 wt% dispersion, and the dispersion was treated with ultrasound for 60 min, during which the temperature was controlled at 30 °C; then a 2 mol / L graphene oxide solution was added to the dispersion and stirred for 10 min, followed by ultrasound treatment for 60 min to obtain a dispersion of cellulose nanofibers and graphene oxide uniformly dispersed; then N2H4·H2O was added to the obtained cellulose nanofiber and graphene dispersion, and stirred to disperse the uniformly dispersed cellulose nanofibers and graphene oxide. After homogenization, the pH value of the system was adjusted to 10 with NH3·H2O, stirred for 5 minutes, the reaction system was sealed, heated to 90°C, reacted for 60 minutes, rinsed with distilled water to neutrality by dialysis method, and freeze-dried to obtain a cellulose nanofiber intercalated graphene composite material; finally, the obtained cellulose nanofiber intercalated graphene composite material was placed in a tubular furnace, a protective gas was introduced, the temperature was increased to 1000°C at a heating rate of 10°C / min and kept for 1 hour, and the temperature was decreased to room temperature at a cooling rate of 10°C / min to obtain a carbon fiber intercalated graphene composite material;

[0075] (3) Material mixing: Weigh the weight portions of nylon 66, carbon fiber, and carbon fiber intercalated graphene composite material, put them into a mixer and mix them evenly, then add the weight portions of modified calcium carbonate, acrylate, zinc stearate, antioxidant, lubricant, and stabilizer, mix them evenly, and obtain a uniformly mixed material;

[0076] (4) Injection molding: The uniformly mixed material in step (3) is put into an injection molding machine, and a plastic anchor bolt is obtained by injection molding and cooling.

[0077] Embodiment 5:

[0078] An anchor bolt, which is different from the embodiment 1 in that the anchor bolt is made of engineering plastics, and the plastics are prepared from the following raw materials in parts by weight:

[0079] 90 parts of nylon 66, 20 parts of carbon fiber, 20 parts of carbon fiber intercalated graphene composite material, 12 parts of modified calcium carbonate, 1 part of acrylate, 1.5 parts of zinc stearate, 2 parts of antioxidant, 1.5 parts of lubricant and 1 part of stabilizer.

[0080] The preparation method of the plastic anchor is as follows:

[0081] (1) Preparation of carbon fiber: Cellulose nanofibers were placed in a tubular furnace, and then a protective gas was introduced. The temperature was raised to 500°C at a rate of 5°C / min and kept at that temperature for 2 h. The temperature was then raised to 1000°C at a rate of 10°C / min and kept at that temperature for 0.5 h. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to obtain carbon fiber material.

[0082] (2) Preparation of carbon fiber intercalated graphene composite materials: cellulose nanofibers were dispersed in an aqueous solution to prepare a 1 wt% dispersion, and the dispersion was treated with ultrasound for 120 min, during which the temperature was controlled at 30 °C; then a 2 mol / L graphene oxide solution was added to the dispersion and stirred for 10 min, followed by ultrasound treatment for 60 min to obtain a dispersion of cellulose nanofibers and graphene oxide uniformly dispersed; then N2H4·H2O was added to the obtained cellulose nanofiber and graphene dispersion, and stirred to disperse the uniformly dispersed cellulose nanofibers and graphene oxide. After homogenization, the pH value of the system was adjusted to 10 with NH3·H2O, stirred for 5 minutes, the reaction system was sealed, heated to 90°C, reacted for 60 minutes, rinsed with distilled water to neutrality by dialysis method, and freeze-dried to obtain a cellulose nanofiber intercalated graphene composite material; finally, the obtained cellulose nanofiber intercalated graphene composite material was placed in a tubular furnace, a protective gas was introduced, the temperature was increased to 1000°C at a heating rate of 10°C / min and kept for 1 hour, and the temperature was decreased to room temperature at a cooling rate of 10°C / min to obtain a carbon fiber intercalated graphene composite material;

[0083] (3) Material mixing: Weigh the weight portions of nylon 66, carbon fiber, and carbon fiber intercalated graphene composite material, put them into a mixer and mix them evenly, then add the weight portions of modified calcium carbonate, acrylate, zinc stearate, antioxidant, lubricant, and stabilizer, mix them evenly, and obtain a uniformly mixed material;

[0084] (4) Injection molding: The uniformly mixed material in step (3) is put into an injection molding machine, and a plastic anchor bolt is obtained by injection molding and cooling.

[0085] In the above embodiments, the antioxidant is antioxidant 1010, the lubricant is glyceryl stearate, and the stabilizer is calcium zinc stabilizer.

[0086] Comparative Example 1:

[0087] A plastic anchor bolt, which is different from Example 3 in that there is no carbon fiber in the component.

[0088] Comparative Example 2:

[0089] A plastic anchor bolt, which is different from Example 3 in that the carbon fiber intercalated graphene composite material is not included in the components.

[0090] Comparative Example 3:

[0091] A plastic anchor bolt, which is different from Example 4 in that the components include 5 parts of carbon fiber and 25 parts of carbon fiber intercalated graphene composite material.

[0092] The different anchor bolts of each embodiment were tested for tensile strength, threaded connection service life, and surface hardness. The threaded connection service life test method is as follows: after the eyebolt is threadedly connected with the plastic anchor bolt, a 2T weight pulling force is applied to it, and the eyebolt is removed. The threaded connection is used once, and the above process is repeated until the eyebolt and the plastic anchor bolt are loosened. The comparison results are shown in Table 1:

[0093] project Tensile strength / Mpa Threaded connection usage times Shore hardness Example 1 130 ≥50 98 Example 2 135 ≥50 100 Example 3 132 ≥50 99 Comparative Example 1 110 10 82 Comparative Example 2 105 8 80 Comparative Example 3 112 12 85

[0094] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An anchor bolt, comprising a bolt barrel (11) having a threaded hole (111) axially disposed at one end thereof, characterized in that: The outer wall of the bolt barrel (11) is fixedly provided with at least one convex ring. The bolt barrel (11) is a plastic part. The outer diameter of the bolt barrel (11) gradually increases from the closed end of the threaded hole (111) to the open end. The plastic is prepared from the following raw materials in parts by weight: 80-90 parts of nylon 66, 10-20 parts of carbon fiber, 15-20 parts of carbon fiber intercalated graphene composite material, 8-12 parts of modified calcium carbonate, 0.5-1 parts of acrylate, 0.8-1.5 parts of zinc stearate, 1-2 parts of antioxidant, 0.8-1.5 parts of lubricant, and 0.5-1 parts of stabilizer; The preparation steps of the anchor bolt are as follows: (1) Preparation of carbon fiber: cellulose nanofibers are placed in a tubular furnace, and then a protective gas is introduced, and the temperature is increased to 300-500°C at a rate of 2-5°C / min and kept at this temperature for 1-3 hours, and then the temperature is increased to 700-1000°C at a rate of 5-10°C / min and kept at this temperature for 0.5-2 hours, and finally the temperature is decreased to room temperature at a rate of 5-10°C / min to obtain a carbon fiber material; (2) Preparation of carbon fiber intercalated graphene composite material: cellulose nanofibers are dispersed in an aqueous solution to prepare a 1wt% dispersion, and the dispersion is treated with ultrasound for 60-120 minutes, during which the temperature is controlled at 20-30°C; then a graphene oxide solution with a molar concentration of 1-2 mol / L is added to the dispersion and stirred for 10-20 minutes, and then ultrasonically treated for 30-60 minutes to obtain a dispersion of cellulose nanofibers and graphene oxide uniformly dispersed; then N2H4·H2O is added to the obtained cellulose nanofiber and graphene dispersion, and after stirring and dispersing uniformly, The PH value of the system is adjusted to 10 by using NH3·H2O, and the mixture is stirred for 5-10 minutes. The reaction system is sealed, heated to 85-90°C, reacted for 60-120 minutes, rinsed with distilled water to neutrality by dialysis method, and freeze-dried to obtain a cellulose nanofiber intercalated graphene composite material; finally, the obtained cellulose nanofiber intercalated graphene composite material is placed in a tubular furnace, a protective gas is introduced, the temperature is increased to 700-1000°C at a heating rate of 5-10°C / min and kept warm for 1-2 hours, and the temperature is decreased to room temperature at a cooling rate of 5-10°C / min to obtain a carbon fiber intercalated graphene composite material; (3) Material mixing: Weigh the weight portions of nylon 66, carbon fiber, and carbon fiber intercalated graphene composite material, put them into a mixer and mix them evenly, then add the weight portions of modified calcium carbonate, acrylate, zinc stearate, antioxidant, lubricant, and stabilizer, mix them evenly, and obtain a uniformly mixed material; (4) Injection molding: The uniformly mixed materials in step (3) are put into an injection molding machine, and a plastic anchor bolt is obtained by injection molding and cooling.

2. The anchor bolt according to claim 1, characterized in that: The side wall of the bolt barrel (11) close to the open end of the threaded hole (111) is extended along the axial direction of the threaded hole (111) to form an extension tube (15), and the inner diameter of the extension tube (15) is larger than the inner diameter of the threaded hole (111).

3. The anchor bolt according to claim 2, characterized in that: The side wall edge of one end of the extension tube (15) away from the plug barrel (11) extends away from the axis to form a flange (14), and the cross section of the flange (14) is triangular.

4. A concrete component, characterized in that: The invention comprises at least one anchor bolt (1) as claimed in any one of claims 1 to 3 which is buried and fixed, and the threaded hole (111) of the anchor bolt (1) is exposed.

5. The concrete component according to claim 4, characterized in that: The concrete component is a tube body (3) of a reinforced concrete structure, and the anchor bolt (1) is fixed on the outer side wall of the tube body (3).

6. The concrete component according to claim 5, characterized in that: A metal sheath (35) is coaxially fixedly disposed on one end of the tube body (3), and a plug-in end (31) matching the metal sheath (35) is disposed on the other end of the tube body (3). A metal protective ring (34) having the same outer diameter as the plug-in end (31) is fixedly disposed on the outer wall of the end portion.

7. The concrete component according to claim 6, characterized in that: An annular groove (32) is provided on the outer wall of the plug end (31) along the circumferential direction.